Analisis Kinerja Dan Efesiensi Sistem Kontrol Motor Induksi 3 Fasa Menggunakan Variable Speed Drive Pada Pompa Proses Fatty Acid Di PT. Permata Hijau Palm Oleo - Bagas Saputra; Ahmad Dani; Beni Satria (CV. Hawari, 2026)
This study investigates the performance and energy efficiency of a three-phase induction motor controlled by a Variable Speed Drive (VSD) in a fatty acid pump system at the Permata Group processing plant. The research is motivated by the increasing need for energy savings and operational reliability in continuous industrial processes where pump load profiles are highly dynamic. The objective of this study is to evaluate the effectiveness of VSD implementation in reducing energy consumption and improving motor operating characteristics under real plant conditions. Data were collected during actual production cycles through direct measurement of electrical and mechanical parameters, including current, voltage, frequency, torque, flow rate, and power consumption. The analysis compares the performance of the pump system before and after the application of VSD, using descriptive statistical analysis and graphical evaluation of motor behavior under various load conditions. The results demonstrate that the application of VSD significantly reduces energy consumption at partial loads while maintaining stable pump output and minimizing mechanical stress. The motor also shows improved operating efficiency and lower thermal loading compared to constant-speed operation. These findings indicate that VSD-based control offers a practical and cost-effective solution for industrial pump systems, especially in fatty acid processing operations where flow demand fluctuates during production. The practical implications are substantial, highlighting opportunities for energy conservation, equipment longevity, and process optimization without compromising product quality or throughput, making the system suitable for broader adoption in similar industrial environments.